Expression of Ralstonia solanacearum type III secretion system is dependent on a novel type 4 pili (T4P) assembly protein (TapV) but is T4P independent. (20th March 2020) - Zhang, Yong; Han, Liangliang; Zhang, Lichun; Xu, Changzheng; Shi, Xiaojun; Hikichi, Yasufumi; Ohnishi, Kouhei
Abstract: Type IV pili (T4P) are virulence factors in various pathogenic bacteria of animals and plants that play important roles in twitching motility, swimming motility, biofilm formation, and adhesion to host cells. Here, we genetically characterized functional roles of a putative T4P assembly protein TapV (Rsc1986 in reference strain GMI1000) and its homologue Rsp0189, which shares 58% amino acid identity with TapV, in Ralstonia solanacearum . Deletion of tapV, but not rsp0189, resulted in significantly impaired twitching motility, swimming motility, and adhesion to tomato roots, which are consistent as phenotypes of the pilA mutant (a known R. solanacearum T4P‐deficient mutant). However, unlike the pilA mutant, the tapV mutant produced more biofilm than the wild‐type strain. Our gene expression studies revealed that TapV, but not Rsp0189, is important for expression of a type III secretion system (T3SS,  a pathogenicity determinant of R. solanacearum ) both in vitro and in planta, but it is T4P independent. We further revealed that TapV affected the T3SS expression via the PhcA–TapV–PrhG–HrpB pathway, consistent with previous reports that PhcA positively regulates expression of pilA and prhG . Moreover, deletion of tapV, but not rsp0189, significantly impaired the ability to migrate into and colonize xylem vessels of host plants, but there was no alteration in intercellular proliferation of R. solanacearum in tobacco leaves, which is similar to the pilA mutant. The tapV mutant showed significantly impaired virulence in host plants. This is the first report on the impact of T4P components on the T3SS, providing novel insights into our understanding of various biological functions of T4P and the complex regulatory pathway of T3SS in R. solanacearum . Abstract : A novel type 4 pili (T4P) assembly protein (TapV) was identified to contribute to full virulence of Ralstonia solanacearum, which affects the T3SS expression via the PhcA–TapV–PrhG–HrpB pathway but is T4P independent.